Responsible growth for the new millennium: integrating society, ecology, and the economy (Washington, DC, 2004)
This report builds on the consensus developed at the August 2002 Johannesburg World Summit on Sustainable Development. It draws on the effort to achieve the Millennium Development Goals by 2015. And it looks beyond, to 2050, to envision a future that is far more prosperous and more equitable than today. This work raises some hard questions: How do we ensure that the progress achieved by 2015 is sustainable? What quality of growth will be required to attain this vision? Long-term thinking is essential in dealing with sustainability issues (economic change, ecological threats). A consensus has emerged about the need to move toward a new development path, one that integrates economic growth with environmental responsibility and social equity. The World Bank has been advocating this vision of responsible growth, together with the concept that poverty reduction is not just an end in itself but also a precondition for peaceful coexistence and ecological survival. The report examines the drivers of growth-agriculture, trade, energy, water, innovation, human development, and social development, as well as the global environment, in particular, forest preservation. It also considers challenges and constraints for socially balanced development.